Expression and purification of recombinant human granulocyte colony‐stimulating factor (rG‐CSF) from Pichia pastoris - Sembiring, Enny Rimita; Fuad, Asrul Muhammad; Suryadi, Herman (Universitas Gadjah Mada, 2024)
Recent advances in biotechnology have sparked global interest in developing biosimilar drugs, particularly those containing physiologically active proteins, such as growth factors and cytokines. The methylotrophic yeast Pichia pastoris can produce and secrete fully active heterologous proteins with strong secretory capacity and low levels of native proteins and has the ability to achieve high cell densities. In this study, a yeast‐based system was used to express and purify recombinant human granulocyte colony‐stimulating factor (rG‐CSF). Cultures were induced every 12 h for 48 h to express rG‐CSF, and parameters such as cell density, media pH, and cell dry weight were observed. Cell density increased along with the corresponding secretion of rG‐CSF during the induction period, as determined by Western blot assay, while the pH of the media remained stable. Ammonium sulfate at different saturation levels was used to precipitate the recombinant protein, with the highest total protein content determined spectrophotometrically at 29.6 µg/mL. Ni‐NTA resin with affinity column purification was used to purify the recombinant protein. The purified protein showed rG‐CSF with a molecular weight of approximately 18 kDa based on SDS‐PAGE analysis and immuno slot blot assay detected in purple. Overall, the study results indicated that the production and purification of rG‐CSF was successful, although optimization was required. The long‐term goal of this research is to discover alternative methods and sources for producing biosimilars of the therapeutic protein rG‐CSF, which can be utilized in the pharmaceutical industry to support health programs, particularly cancer treatment.